As fake news e a nova ordem (des)informativa na era da pós-verdade: Manipulação, Polarização, Filter Bubbles - João Figueira (Investigação, 2019)
The debate about the fake news is now rejoined by two factors: rise of protagonists outside the field of politics who now dominate the publicized media space and the role of social networks and the Internet that vie for journalism to its old communicational and informative centrality. Recent studies have also shown that in the current digital environment marked by the influence of social networks, it is through Facebook that the most information traffic is verified, although the so-called "hard news" circulate preferentially through Twitter. This means a profound change also in the way the policy communicates and gains a renewed centrality. Populism and the construction of post-truths were breaking new ground for affirmation, challenging democracy and the exercise of rigorous, demanding and enlightened information. Researchers from a dozen Portuguese and Brazilian universities observe and reflect, in a transdisciplinary way, about these new phenomena, seeking to analyze causes and consequences, while presenting case studies and proposing solutions.